Dinámica espacio-temporal de oxígeno-temperatura en los lagos Zempoala y Tonatiahua - Quiroz Castelán, Héctor; Mondragón Eslava, Olivia; Molina Astudillo, Isela; García Rodríguez, Judith; Díaz Vargas, Migdalia (Acta Universitaria, 2008)
The nictimeral studies are particularly important in the tropics, to know the ecology variations in diurnal cycles and not only in seasonal cycles. And this is not only from the conceptual point of view, rather for the application of management plans in different environments. The objective was to analyze the variations of dissolved oxygen, percentage of saturation and temperature in the water column during nictimeral cycles, in the lakes of Zempoala and Tonatiahua located in the National Park Lagunas de Zempoala. The greater values of oxygen appeared in Zempoala, and the temperature was analogous in both lakes according to the total values average. Variation of the parameters was directly influenced by the seasonal changes, its morphometry and surroundings. Zempoala lake was considered itself as meromictic with tendencies to warm monomictic and Tonatiahua as warm monomictic.
Keywords: Array; Array; Array; Array